P Pola Penelusuran Informasi oleh Pemustaka dengan Mesin Pencari Google di Perpustakaan Universitas Islam Negeri Mataram - Nuraeni Mansyur (IJAL (Indonesian Journal of Academic Librarianship), 2024)
This research examines the search patterns carried out by users in the Mataram State Islamic University library. The goals of this research is to analyze information search patterns carried out by users using the Google search engine. The method used in this research is descriptive qualitative. Data collection was carried out by interviews, observation and documentation. Based on the research results, it can be concluded that the search patterns carried out by users at the Mataram State Islamic University Library tend to use simple search features. The features that can be used are image, news, video and calculator search features and file extensions. In using these features, users only enter keywords directly in the search column then select the image tab to search for images, videos to search for videos, news. In advanced searches, the feature that can be used is searching based on file type by adding the file extension at the end. searched keywords (.doc, .docx, .pdf, etc.). Readers who use this type of file did not access it via advanced search, but directly enter keywords and the file extension in the search column.